Evaluation of a Feed Plant Additive for Coocidiosis Control in Broilers Herbals for Coccidiosis Control - C Sánchez-Hernández; JA Castañeda-Gómez del Campo; L Trejo-Castro; GD Mendoza-Martínez; A Gloria-Trujillo (Brazilian Journal of Poultry Science, 2019)
ABSTRACT Coccidiosis negatively impacts health and productive performance in broilers. Anticoccidial resistance has prompted alternatives to prevent and control this disease. Therefore, the objective of this study was to evaluate a plant feed additive consisting of Acacia concinna containing saponins (Peptasan®) and compare its effectiveness with salinomycin in terms of performance of broilers challenged with Eimeria. In the first experiment, 300 Ross chicks (1 day old) were randomly distributed into a negative (uninfected and untreated), and positive control group (infected and untreated), and three levels of dietary Peptasan® (500, 750 and 1000 ppm). In the second experiment, the same number of chicks were distributed in two control groups (negative and positive), two levels of Peptasan® (500 and 750 ppm) and one level of salinomycin (550 ppm). In both experiments chicks were challenged at day 21 of age with 100,000 oocysts of Eimeria acervulina, 50,000 oocysts of Eimeria maxima and 50,000 oocysts of Eimeria tenella. Dietary Peptasan® improved productive performance, reduced mortality and the number of oocysts in feces, as well as increased yellow pigmentation of the skin of challenged chickens. The plant feed additive Peptasan® containing Acacia concinna can be effectively used for preventing coccidiosis in broilers.